Predictors of (in)efficiencies of Healthcare Expenditure Among the Leading Asian Economies – Comparison of OECD and Non-OECD Nations - Jakovljevic M; Sugahara T; Timofeyev Y; Rancic N (Dove Medical Press, 2020)
Mihajlo Jakovljevic,1– 3 Takuma Sugahara,2 Yuriy Timofeyev,4 Nemanja Rancic5,6 1Department of Global Health Economics and Policy, Faculty of Medical Sciences, University of Kragujevac, Kragujevac, Serbia; 2Institute of Comparative Economics, Hosei University, Tokyo, Japan; 3N.A.Semashko Department of Public Health and Healthcare, I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russia; 4National Research University Higher School of Economics, Moscow, Russia; 5Centre for Clinical Pharmacology, Military Medical Academy, Belgrade, Serbia; 6Faculty of Medicine of the Military Medical Academy, University of Defence, Belgrade, SerbiaCorrespondence: Mihajlo JakovljevicDepartment of Global Health Economics and Policy, Faculty of Medical Sciences, University of Kragujevac, Kragujevac 34000, SerbiaTel +381 34306 800Email sidartagothama@gmail.comPurpose: The goal of this study was to assess the effectiveness of healthcare spending among the leading Asian economies.Methods: We have selected a total of nine Asian nations, based on the strength of their economic output and long-term real GDP growth rates. The OECD members included Japan and the Republic of Korea, while the seven non-OECD nations were China, India, Indonesia, Malaysia, Pakistan, the Philippines, and Thailand. Healthcare systems efficiency was analyzed over the period 1996– 2017. To assess the effectiveness of healthcare expenditure of each group of countries, the two-way fixed effects model (country- and year effects) was used.Results: Quality of governance and current health expenditure determine healthcare system performance. Population density and urbanization are positively associated with a healthy life expectancy in the non-OECD Asian countries. In this group, unsafe water drinking has a statistically negative effect on healthy life expectancy. Interestingly, only per capita consumption of carbohydrates is significantly linked with healthy life expectancy. In these non-OECD Asian countries, unsafe water drinking and per capita carbon dioxide emissions increase infant mortality. There is a strong negative association between GDP per capita and infant mortality in both sub-samples, although its impact is far larger in the OECD group. In Japan and South Korea, unemployment is negatively associated with infant mortality.Conclusion: Japan outperforms other countries from the sample in major healthcare performance indicators, while South Korea is ranked second. The only exception is per capita carbon dioxide emissions, which have maximal values in the Republic of Korea and Japan. Non-OECD nations’ outcomes were led by China, as the largest economy. This group was characterized with substantial improvement in efficiency of health spending since the middle of the 1990s. Yet, progress was noted with remarkable heterogeneity within the group.Keywords: Asia, health expenditure, healthy life expectancy, infant mortality, nutrition, population health outcomes